Rhetoric and Logical Argumentation of the Famous Preacher KH. Anwar Zahid - Linda Nurazizah (Konsultan Jurnal Ilmiah Indonesia, 2024)
Quoting the book on the science of preaching by Prof. Dr. Moh. Ali Aziz. M. Ag,. The obligation to preach, as stated by A. Hasyimi, is not actually a special group task where other people are free from responsibility. As Muslims are given responsibilities such as prayer, zakat, fasting, so every Muslim also transfers faith in an empty heart to guide people to the straight path. The book explains that the law of preaching for Muslims can be fardhu 'ain and fardhu kifayah (together). This opinion was pioneered by Muhammad Abu Zahrah. According to him, fardhu 'ain is da'wah carried out individually. Meanwhile fardhu kifayah is da'wah carried out collectively. As we have seen, preachers who are famous throughout Indonesia, one of them is KH. Anwar Zahid, a famous preacher from East Java, originally